2018
DOI: 10.1038/s41598-018-30570-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of candidate elements for development of spectral photon-counting CT specific contrast agents

Abstract: Spectral photon-counting computed tomography (SPCCT) is a rapidly emerging imaging modality that provides energy-dependent information on individual x-ray photons, leading to accurate material decomposition and simultaneous quantification of multiple contrast generating materials. Development of SPCCT-specific contrast agents is needed to overcome the issues with currently used iodinated contrast agents, such as difficulty in differentiation from calcified structures, and yield SPCCT’s full promise. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 66 publications
3
91
0
1
Order By: Relevance
“…Tracking therapeutic cells with CT is an emerging field (reviewed in (12)). The main originality of spectral CT compared to other non-spectral X-ray-based approaches (µCT, clinical CT or synchrotron radiation CT (41)) is represented by its specificity with regard to the detection of gold or other elements with K-edge energies in the appropriate range (~40 -100 keV) (42)(43)(44). Pioneering work for the specific imaging of macrophages with SPCCT was published 10 years ago in a mouse model of atherosclerosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Tracking therapeutic cells with CT is an emerging field (reviewed in (12)). The main originality of spectral CT compared to other non-spectral X-ray-based approaches (µCT, clinical CT or synchrotron radiation CT (41)) is represented by its specificity with regard to the detection of gold or other elements with K-edge energies in the appropriate range (~40 -100 keV) (42)(43)(44). Pioneering work for the specific imaging of macrophages with SPCCT was published 10 years ago in a mouse model of atherosclerosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no significant difference of diagnostic performance was found between the 2 injection protocols, probably because of the low contrast enhancement of peritoneal lesions observed, and because the injection protocol did not influence the POI and the diagnostic quality www.nature.com/scientificreports/ score. Regarding gadolinium contrast agent, our study adds to growing data demonstrating that it is a good candidate for SPCCT imaging as it allows good separation from body tissue and iodine based on its K-edge 29,33,36,68 . Taking into account that the amount of IV gadolinium of the protocol B was higher than the recommended clinical doses in MRI and the knowledge of gadolinium tissue deposition in brain and bone 69 , protocol A with IV appears to be more suitable for clinical research.…”
Section: Discussionmentioning
confidence: 84%
“…Dualor multicontrast imaging with other contrast agents, such as ytterbium, tantalum, tungsten, and gold with K-edges of 61.3, 67.4, 69.5, and 80.7 keV, respectively, have also been proposed, since their K-edges are also located within the clinical x-ray spectrum. [35][36][37][38] Their quantitative accuracy and dose efficiency remain to be investigated. Last but not the least, the three-material model in the phantom study used pure water as the background basis material, which is much simplified compared to that in realistic clinical tasks, where the background material is soft tissue or blood.…”
Section: Discussionmentioning
confidence: 99%